Full-wave rectifiers using operational amplifiers and resistors - Surakampontorn, W.; Jutaviriya, S.; Apajinda, T. (My University, 1989)
An alternative scheme for realizing a Full-wave rectifier is described in this note. The realization method uses the inherited class AB complementary stage of a general-purpose operational amplifier (op amp) as a means to perform a rectifier action. Therefore, the rectifier circuits comprise only op amps and resistors. © 1989 Taylor & Francis Ltd.